2018
DOI: 10.1159/000495491
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy Can Be Treated with Calcium Dobesilate by Alleviating the Chronic Inflammatory State and Improving Endothelial Cell Function

Abstract: Background/Aims: Diabetic kidney disease (DKD) is a leading cause of end-stage renal disease. However, no effective treatments for this disease are available. Calcium dobesilate (CaD) is widely used to treat diabetic retinopathy. DKD and retinopathy often co-exist and have similar mechanisms of pathogenesis. The aim of the present study was to elucidate the safety and efficacy of CaD in the treatment of DKD. Methods: In the prospective randomised controlled study, 100 DKD from Type 2 diabetes mellitus (DM) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…In recent years, many studies have shown that metabolic syndrome is associated with inflammatory mediators, the most representative of which is hs-CRP: elevated serum hs-CRP level has been found in patients with diabetes, hypertension, obesity, hyperlipidemia, and even cardiovascular diseases [15]. PTX3 is similar to CRP in structure and function and has a good correlation with hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have shown that metabolic syndrome is associated with inflammatory mediators, the most representative of which is hs-CRP: elevated serum hs-CRP level has been found in patients with diabetes, hypertension, obesity, hyperlipidemia, and even cardiovascular diseases [15]. PTX3 is similar to CRP in structure and function and has a good correlation with hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our experiments show that CaD prevents the increase and upregulation/activation of several pro-inflammatory cytokines (IL-6, CXCL1, IL-1ß, TNF-α, and MCP-1) that play a significant role in renal-disease progression. Although the anti-inflammatory properties of CaD have been previously reported [25,59,60], to the best of our knowledge, our report is the first involving a diabeticnephropathy animal model. These findings are therefore important due to the pivotal role of inflammation in the pathogenesis of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 74%
“…Wang et al, recently published that CaD supressed renal interstitial fibrosis by promoting anti-apoptotic effects through Sirt1/p53 signaling pathway 26 . CaD was also reported to attenuate diabetes-induced endothelial dysfunction and chronic inflammation in diabetic nephropathy via reducing inflammatory and endothelial dysfunction markers 27 . However; none of the markers mentioned above was investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits inflammatory factors and improves circulation by lowering blood viscosity, supressing platelet activity and capillary permeability. In diabetic nephropathy patients, improved CaD endothelial cell function and chronic inflammation 8 . CaD was reported to inhibit TGFb and bFGF in a diabetic nephropathy model and basal cell carcinoma respectively 9,10 .…”
Section: Introductionmentioning
confidence: 99%